Pendekatan Contextual Teaching and Learning (CTL) berbantuan aplikasi scratch pada kemampuan koneksi matematis siswa kelas VIII - Agustin, Rosiana; Minarti, Eva Dwi; Riajanto, Marchasan Lexbin Elvi Judah (IKIP Siliwangi, 2025)
This research is to find out whether the mathematical connection abilities of students who use the Contextual Teaching and Learning approach assisted by the Scratch application are better than students who use ordinary learning, a scientific approach. This type of research is quantitative research with a quasi-experimental design in the form of Pretest Posttest Nonequivalent Control. Class VIII students of SMP Negeri 4 Cimahi were the subjects of this research. Class VIII-K is the sample for the experimental class and class VIII-L is the control class. The test instrument used is 4 questions on mathematical connection abilities. The data analysis techniques in this research are normality test, homogeneity test and independent two-sample t-test. The research results show that the mathematical connection abilities of students who use the Contextual Teaching And Learning learning model are better than students who use the normal approach. The average ability of students is moderate because students do not focus on studying and steal time during learning for other activities.